2019
DOI: 10.1017/s1366728918001220
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy between heritage speakers' use of suprasegmental cues in the perception and production of Spanish lexical stress

Abstract: This study investigates Spanish heritage speakers' perception and production of Spanish lexical stress. Stress minimal pairs in various prosodic contexts were used to examine whether heritage speakers successfully identify the stress location despite varying suprasegmental cues (Experiment 1) and whether they use these cues in their production (Experiment 2). Heritage speakers' performance was compared to that of Spanish monolinguals and English L2 learners. In Experiment 1, the heritage speakers showed a clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 90 publications
6
39
0
Order By: Relevance
“…Interestingly, Kim (2019) found what can be seen as a consistent pattern of results while investigating the production and perception of Spanish lexical stress among heritage speakers (i.e., speakers who learned Spanish from birth, but now use it only at home and use English in all other contexts). Comparing their production to that of monolingual Spanish speakers and of English-L1 learners of Spanish, Kim (2019) found that heritage speakers' production of Spanish lexical stress patterns with that of English-L1 learners of Spanish and not with that of monolingual Spanish speakers. On the other hand, Spanish heritage speakers' perception of Spanish lexical stress matched that of monolingual Spanish speakers and not that of English-L1 learners.…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…Interestingly, Kim (2019) found what can be seen as a consistent pattern of results while investigating the production and perception of Spanish lexical stress among heritage speakers (i.e., speakers who learned Spanish from birth, but now use it only at home and use English in all other contexts). Comparing their production to that of monolingual Spanish speakers and of English-L1 learners of Spanish, Kim (2019) found that heritage speakers' production of Spanish lexical stress patterns with that of English-L1 learners of Spanish and not with that of monolingual Spanish speakers. On the other hand, Spanish heritage speakers' perception of Spanish lexical stress matched that of monolingual Spanish speakers and not that of English-L1 learners.…”
Section: Introductionsupporting
confidence: 63%
“…These results cohere with those of Cutler et al (1992), who found an effect of language dominance among simultaneous bilinguals' use of prosodic cues in word/syllable spotting tasks. Moreover, these results demonstrate that the production of native-like F0 ratios in English is more variable than previously expected, and that native exposure to English is not sufficient to maintain native-like production of F0 in English if exposed to another language with different prosodic patterns (see Kim, 2019 for similar effects on Spanish lexical stress production.) Nonetheless, F0 production of the English-L1 speaker group (who learned English from birth and French only later in life) was not affected by their relative language dominance, which might give the impression that F0 production in their L1 was somewhat immune to influences from their L2.…”
Section: B Relative Language Dominance Effectssupporting
confidence: 50%
See 2 more Smart Citations
“…Compared to this, less research has been done in phonological domains, most likely given that positive effects of early exposure have been attested on heritage language pronunciation (Au, Knightly, Jun & Oh, 2002;Knightly, Jun, Oh & Au, 2003). Nevertheless, recent studies on heritage language phonology discuss the existence of a "heritage accent" (Au, Oh, Knightly, Jun & Romo, 2008;Lloyd-Smith, Einfeldt & Kupisch, 2020;Stangen, Kupisch, Proietti Ergün & Zielke, 2015) and found deviations from monolingual norms at both segmental (Amengual, 2012(Amengual, , 2016Elias, McKinnon & Milla-Muñoz, 2017;Godson, 2004;Kissling, 2018;Ronquest, 2013;Willis, 2005) and suprasegmental levels (Chang, Yao, Haynes & Rhodes, 2011;Colantoni, Cuza & Mazzaro, 2016;Henriksen, 2016;Kim, 2019;Kim, 2020). For instance, Au et al (2008) found that Spanish heritage speakers, regardless of whether they regularly used Spanish during childhood, sounded more native-like than late L2 learners, but when compared with non-heritage native speakers, their speech was perceived to have a stronger foreign accent.…”
Section: Introductionmentioning
confidence: 99%